Positioning, power, and identity transformation among English teachers in Chinese private universities: a narrative inquiry - Jin, Qi; Kim, Jungyin (Frontiers in Psychology, 2026)
IntroductionAlthough language teacher identity has been widely examined in public university contexts, relatively little is known about how teachers in resource-constrained private institutions navigate role ambiguity and emotional strain. This study aims to investigate how English teachers at a private university construct and transform their teacher identities over time within structural and discursive constraints.MethodsThis study utilized qualitative methods and a narrative inquiry across a multiple case study framework. Data were collected from three English teachers through semi-structured interviews, classroom and meeting observations, and netnographic methods. This study traced the pre-positioning, negotiated positioning, and performed positioning of identity construction through positioning theory, which explores how individuals assume professional roles through words and actions. The willingness, capability, power (WCP) framework was used to analyze how teacher identity transformation was influenced by willingness to act, skills to act, and power to act.Results/findingsThe findings from RQ1 identified three themes. In pre-positioning, all three participants’ entry into the teaching profession was accidental and reflected gendered discourses. Negotiated positioning manifested as role conflict, emotional costs, and adaptive reframing. Within the performed positioning, teachers stabilized their identities through specialization and strategic boundary-setting. RQ2 identified four WCP-based identity trajectories: Unfulfilled Initiative, where strong motivation was hindered by limited power; Adaptive Reframing, which involved adjusting expectations and teaching methods to maintain engagement; The Residual Functionality reflected the emotional withdrawal amid disempowerment; and Reinforcing Engagement, which manifested as the alignment of motivation, capability, and recognition to support sustained professional growth.DiscussionThis study provides a power-focused and temporally grounded account of identity transformation in the context of resource-constrained private institutions. The research demonstrates that identity is a dynamic and emotionally mediated process. Two context-specific concepts, discursively orphaned identity and performed stagnation, highlight subtle forms of disempowerment that are often overlooked in formal policy discourse. The findings suggest that institutional support should go beyond material resources to encompass discursive inclusion and symbolic affirmation. This provides theoretical insights for future research and policymaking in the field of language teacher education in resource-constrained private higher education settings.